Using Visual Data in Qualitative Research : (2008) Marcus Banks. Los Angeles, CA: Sage. - Silpe, Shane (Journal of MultiDisciplinary Evaluation, 2017)
A review of the book Using Visual Data in Qualitative Research by Marcus Banks, published in 2008 by Sage.